Aggregation‐Induced Emission (AIE) in Ag−Au Bimetallic Nanocluster. Issue 15 (23rd February 2018) - Jin, Shan; Liu, Wei; Hu, Daqiao; Zou, Xuejuan; Kang, Xi; Du, Wenjun; Chen, Shuang; Wei, Shiqiang; Wang, Shuxin; Zhu, Manzhou
Abstract: Herein we report the synthesis and structure determination of a non‐fluorescent Au4 Ag5 (dppm)2 (SAdm)6 (BPh4 ) (dppm=bis(diphenylphosphino)methane and HSAdm=1‐adamantane mercaptan) nanocluster in methanol with extremely strong AIE when aggregating to the solid state (i.e., film or crystal). This phenomenon was rarely reported in structural determined noble metal nanoclusters. The extended X‐ray absorption fine structure (EXAFS) measurement ruled out the hypothesis that the luminescence originated from the structure change in different states. Besides, the crystal structure (determined by X‐ray diffraction) revealed that the tightly combined left‐ and right‐handed enantiomers induced the strong restriction of intramolecular motions (RIM), which may have an impact on aggregation‐induced emission. Abstract : Small and bright : The synthesis and structural determination of chiral Au4 Ag5 (dppm)2 (SAdm)6 (BPh4 ) nanocluster is reported. Interestingly, this nanocluster was non‐luminescent in the dissolved state but highly luminescent in the solid state (i.e., film or crystal). The extended X‐ray absorption fine structure (EXAFS) measurement ruled out that the luminescence origin from structure alteration in the different states.